2008
DOI: 10.1002/chem.200800180
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of the Unusual Helix Stability of a De Novo Engineered Vascular Endothelial Growth Factor (VEGF) Mimicking Peptide

Abstract: Helix stability: Understanding helix stability and formation is a prerequisite to elucidate the mechanism of protein folding and design helix peptides with specific activity. Herein, we analyze the thermal behaviour of a designed, α-helical, bioactive peptide, composed only of natural amino acids. This peptide shows an unusual thermal stability, in which the N-terminal region and a hydrophobic interaction play a major role

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 17 publications
(16 reference statements)
4
38
0
Order By: Relevance
“…1C). The reported bioactive secondary structure of the VEGF-mimetic sequence is α-helical (30,31). CD of the VEGF PA revealed a signal characteristic of α-helix (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…1C). The reported bioactive secondary structure of the VEGF-mimetic sequence is α-helical (30,31). CD of the VEGF PA revealed a signal characteristic of α-helix (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, a number of synthetic strategies have emerged to modulate angiogenesis through small molecules or peptides and have been developed to antagonize receptors for cancer therapies or to promote angiogenesis by signaling through these receptors (28,29). Currently, only one synthetic oligopeptide has been demonstrated to mimic VEGF through the activation of its receptors (30,31). This peptide was designed based on the native α-helical receptor-binding domain of VEGF and was shown to mimic native VEGF through activation of VEGF receptors.…”
mentioning
confidence: 99%
“…Initially, we focused on the VEGF helix 17-25 (29). The designed 15-mer peptide assumes in water a well defined helical conformation and presents a remarkable thermal stability (30,31). It binds and activates VEGF receptors and shows VEGF-like activity in vitro (29) and in vivo (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…107 Similar to the peptide sequence in native VEGF, 104,108 the sequence folded into an alpha-helical conformation. It was found that the VEGF-mimetic peptide was able to bind the VEGF receptors of HUVECs and thereby improved migration, proliferation and survival of the cells.…”
Section: Cell Signaling By Supramolecular Materialsmentioning
confidence: 99%